Mitochondrial DNA deletions are abundant and cause functional impairment in aged human substantia nigra neurons - Kraytsberg, Yevgenya; Kudryavtseva, Elena; McKee, Ann C; Geula, Changiz; Kowall, Neil W; Khrapko, Konstantin (Nature genetics, 2006)
Using a novel single-molecule PCR approach to quantify the total burden of mitochondrial DNA (mtDNA) molecules with deletions, we show that a high proportion of individual pigmented neurons in the aged human substantia nigra contain very high levels of mtDNA deletions. Molecules with deletions are largely clonal within each neuron; that is, they originate from a single deleted mtDNA molecule that has expanded clonally. The fraction of mtDNA deletions is significantly higher in cytochrome c oxidase (COX)-deficient neurons than in COX-positive neurons, suggesting that mtDNA deletions may be directly responsible for impaired cellular respiration.